Preconception maternal exposure to Nippostrongylus brasiliensis transfers protection against Nb to her offspring - Darby, Matthew G (Institute of Infectious Disease and Molecular Medicine, 2016)
In early life the immature immune system has a reduced ability to control infection. This susceptibility is offset by transfer of protective immune components from the mother. Helminth infections are widespread and can have a long lasting influence on host immunity. Children of mothers exposed to helminth infections may display T cell sensitization to endemic helminth infections and associations have been made between maternal helminth infection and altered immune responses to childhood diseases and vaccinations. This shows that helminth-modified maternal immunity may imprint on early offspring immune development in-utero or through breast milk in the form of transfer of, for example, antibodies, cytokines and lymphocytes. Our study shows that, in mice, maternal infection with the helminth Nippostrongylus brasiliensis is not only associated with a passive transfer of antigen specific antibody(IgG1) but also inherently alters offspring immunity, increasing offspring cytokine production, alveolar macrophages, lung neutrophils and B cell population development and proliferation. Pups born to N. brasiliensis exposed mothers also had increased populations of lung and spleen CD4+ cells and higher subpopulations of central memory and effector CD4+ cells compared to pups born to naive mothers.